Towards a Deeper Understanding of Agricultural Production Systems in Sweden Linking Farmers Logics with Environmental Consequences and the Landscape - Kristina Marquardt; Camilla Eriksson; Brian Kuns (Rural Landscapes: Society Environment History, 2022)
Farm restructuring is a continuous on-going process supported by national agricultural policy in Sweden; while striving for more efficient farms in terms of labor and yields, farms enlarge their holdings of arable land and animals. The environmental consequences of more intensive land uses have in turn stimulated environmental policies to deal with negative environmental consequences. In this paper we argue that an underlying problem with both of these policy approaches is that they primarily emphasize specific components of farms and fail to see the farm as an interconnected system. In this paper we therefore focus on the farm as a system and on the systemic role of farming in the broader landscape. We develop a theoretical framework of farming logics which help to better understand agricultural production systems. Drawing on 34 semi-structured interviews with farmers, we divide the farms into three farming logic categories: I) production vanguards; II) landscape stewards; and III) environmental vanguards. We use these categories to analyze the role of key aspects such as size, intensity of production, specialisation, how farmer preferences and knowledge influence land use systems, and interactions of these with the local landscape. The findings show how farms that on the one hand share some basic characteristics can display quite different farming logics and vice versa. We argue that these farming logics offer a potentially positive diversity in farming approaches, with complementary and mutually dependent roles in Swedens overall food system.